The Uses of Literature Life in the Socialist Chinese Literary System - Link, Perry (Princeton University Press, 2022)
Why do people in socialist China read and write literary works? Earlier studies in Western Sinology have approached Chinese texts from the socialist era as portraits of society, as keys to the tug-of-war of dissent, or, more recently, as pursuit of "pure art." The Uses of Literature looks broadly and empirically at these and many other "uses" of literature from the points of view of authors, editors, political authorities, and several kinds of readers. Perry Link, author of Evening Chats in Beijing, considers texts ranging from elite "misty" poetry to underground hand-copied volumes (shouchauben) and shows in concrete detail how people who were involved with literature sought to teach, learn, enjoy, explore, debate, lead, control, and resist. Using the late 1970s and early 1980s as an entree to the workings of China's "socialist literary system," the author shows how that system held sway from 1950 until around 1990, when an encroaching market economy gradually but fundamentally changed it. In addition to providing a definitive overview of how the socialist Chinese literary system worked, Link offers comparisons to the similar system in the Soviet Union. In the final chapter, the book seeks to explain how the word "good" was used and understood when applied to literary works in such systems. Combining aspects of cultural and literary studies, The Uses of Literature will reward anyone interested in the literature of modern China or how creativity is affected by a "socialist literary system.